Exosomal miR-486-5p derived from human placental microvascular endothelial cells regulates proliferation and invasion of trophoblasts via targeting IGF1 - Ma, Ruixia; Liang, Zhijiang; Shi, Xiaomei; Xu, Linli; Li, Xiaowei; Wu, Jinhua; Zhao, Lina; Liu, Guocheng (Human cell : official journal of Human Cell Research Society, 2021)
Preeclampsia (PE) is a serious complication of pregnancy. Exosomes are known to be upregulated in PE. In this study, we sought to investigate the effect of miR-486-5p from human placental microvascular endothelial cells, on the function of trophoblast cells. To investigate the function of human placental microvascular endothelial cell (HPVEC)-derived exosomes on trophoblast cells, HPVECs were treated with hypoxia/reoxygenation (H/R). The separation efficiency of exosomes was determined by transmission electron microscopy, nanosight and Western blot. Cell Counting Kit-8, EdU staining, wound-healing, and transwell assay were performed to detect the effect of exosomally transferred miR-486-5p inhibitor on proliferation, migration and invasion of trophoblast cells. MiRDB and dual-luciferase report assay were used to find the target of miR-486-5p. Our data revealed that miR-486-5p was significantly upregulated in H/R-treated HPVEC-Exo, and miR-486-5p was enriched in HPVEC-Exo. miR-486-5p inhibitor carried by HPVEC-Exo significantly inhibited the proliferation, migration and invasion of trophoblast cells. Insulin-like growth factor 1 (IGF1) was found to be the target of miR-486-5p, and IGF1 overexpression notably reversed the effect of miR-486-5p inhibitor from HPVEC-Exo on trophoblast cell function. In summary, H/R-treated HPVEC-derived exosomally expressing miR-486-5p inhibitor significantly inhibited the proliferation, migration and invasion of trophoblast cells via downregulation of IGF1. The findings from the present study may be useful in the development of treatments for PE.